Justice: Deconstruction and Hermeneutics : Interviews with Contemporary Thinkers - Atilla, Sema Cevirici, (Social and Critical Theory ;, 2025)
The pursuit of justice is an unending journey. It is the name of an impending promise that we always pray for, hope for, and sincerely desire but cannot quite see its fulfilment. Justice always encourages openness to the future and refuses to be confined to a particular definition. It occurs at different times with various demands and perspectives, and it cannot be reduced to a single definition and a single norm. This is precisely why this book consists of philosophical conversations that aim to expose the different faces of justice and to bring together the thoughts and concerns of thinkers talking about justice from different contexts. The interviews address issues such as God, ethics, otherness, anarchism, the refugee crisis, law, democracy and human rights in the framework of their relation to justice. The book is an invitation to everyone who wants to discuss the demands of justice in different contexts and witness the different faces of justice.